Sir John Beddington on food production and climate change - Beddington, J.R. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Is there an appreciation for how existing challenges to food production will be greatly intensified by climate change? Sir John Beddington the chair of the Commission on Sustainable Agriculture and Climate Change.